The impact of Greek thought on the intellectual renaissance in Europe - Qabaha, Mahmoud Gawdat (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the impact of Greek thought on the intellectual renaissance in Europe. For the purpose of achieving this goal, the study adopted the historical and analytical descriptive curriculum. The study concluded several findings, most notably: Changes in the European Community in several areas have come not from a vacuum but from the accumulation of previous civilizations, which represented a legacy and harvest that constitutes a cornerstone of the European intellectual renaissance in several areas. The most prominent recommendations of this study are: Not to lose sight of the ancient historical legacy of Greek civilization, which formed the basis of the European intellectual renaissance, Study the psychological and social impact of changes in preceding hatred on individuals in an effort to build on past experiences, extrapolate reality and predict the effects of future changes on humanity, Encouraging researchers to navigate past civilizations from different angles civilizations remain an inexhaustible legacy.
Keywords: Greek civilization; European renaissance